2001
DOI: 10.1182/blood.v98.3.667
|View full text |Cite
|
Sign up to set email alerts
|

The p38 mitogen-activated protein kinase pathway plays a critical role in thrombin-induced endothelial chemokine production and leukocyte recruitment

Abstract: Thrombin, the terminal serine protease in the coagulation cascade, is a proinflammatory molecule in vivo and induces endothelial activation in vitro. The cellular signaling mechanisms involved in this function are unknown. The role of the p38 mitogen-activated protein kinase (MAPK) signaling pathway in thrombin-induced chemokine production was studied. Phosphorylation of both p38 MAPK and its substrate, ATF-2, was observed in human umbilical vein endothelial cells (HUVECs) stimulated with thrombin, with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 47 publications
7
62
3
1
Order By: Relevance
“…mCRP stimulated rapid phosphorylation of this kinase, and the specific p38 MAPK inhibitor SB203580 markedly inhibited HCAEC responses to mCRP, although the inhibition was incomplete. These results are consistent with those observed with SB203580 on thrombininduced endothelial chemokine production and ICAM-1 expression, 32,33 and suggest involvement of other intracellular signaling mechanism(s). Unlike in neutrophils, 18,19 mCRP does not appear to activate the MAPK kinase and phosphatidylinositol 3-kinase pathways in HCAECs, because there was no reduction in the presence of PD98059 and wortmannin.…”
Section: Khreiss Et Al Loss Of Symmetry In Crp and Inflammation 2019supporting
confidence: 82%
“…mCRP stimulated rapid phosphorylation of this kinase, and the specific p38 MAPK inhibitor SB203580 markedly inhibited HCAEC responses to mCRP, although the inhibition was incomplete. These results are consistent with those observed with SB203580 on thrombininduced endothelial chemokine production and ICAM-1 expression, 32,33 and suggest involvement of other intracellular signaling mechanism(s). Unlike in neutrophils, 18,19 mCRP does not appear to activate the MAPK kinase and phosphatidylinositol 3-kinase pathways in HCAECs, because there was no reduction in the presence of PD98059 and wortmannin.…”
Section: Khreiss Et Al Loss Of Symmetry In Crp and Inflammation 2019supporting
confidence: 82%
“…A large body of evidence suggests that thrombin and its receptors (PARs), particularly PAR1, play a role in endothelial barrier disruption, promoting the sticking of leukocytes and monocytes/macrophages to the endothelium and their infiltration into the subendothelial space (4,6,20,21), which are the hallmarks of atherogenesis (57). An enhanced expression of PAR1 in the regions of inflammation associated with macrophage influx, smooth muscle cell proliferation, and mesenchymal-like intimal cells further supports a role for its involvement in atherosclerosis (58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation appears to be the major factor underlying the atherogenesis, and it may be initiated with endothelial cell dysfunction, leading to leukocyte adhesion, ROS production, and low density lipoprotein (LDL) oxidation (2,3). Several studies have demonstrated that the recruitment of leukocytes and monocytes/macrophages to the site of vascular injury is dependent on the production of cytokines and adhesion molecules by the dysfunctional endothelium, resulting in their adherence to the endothelium and their subsequent transendothelialization (4,5). In addition, the injured/dysfunctional endothelium may expose the underlying vascular matrix to the flowing blood, which can lead to activation of platelets and production of thrombin (6,7).…”
mentioning
confidence: 99%
“…Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45). Furthermore, thrombin, factor Xa, and fibrin degradation products are all potent inducers of the inflammatory response (46)(47)(48)(49)(50). Hence, the presence of microparticles in synovial fluid may facilitate not only coagulation, but also inflammation via direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%